2007
DOI: 10.1097/wnr.0b013e3280d943b9
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile activation of the auditory cortices in deaf versus hearing adults

Abstract: Neuroplastic changes in auditory cortex as a result of lifelong perceptual experience were investigated. Adults with early-onset deafness and long-term hearing aid experience were hypothesized to have undergone auditory cortex plasticity due to somatosensory stimulation. Vibrations were presented on the hand of deaf and normal-hearing participants during functional MRI. Vibration stimuli were derived from speech or were a fixed frequency. Higher, more widespread activity was observed within auditory cortical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
135
3
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 25 publications
10
135
3
3
Order By: Relevance
“…For example, Neville et al reported changes in evoked visual response in congenitally deaf persons and interprfeted it as a neuroplastic change, in which visual input invades unused areas of the auditory cortex. [27] These fi nding were later confi rmed in studies of subjects with single sensory deprivation (auditory or visual) using neuroimaging techniques with greater spatial resolution (fMRI and PET), [5,[28][29][30] which demonstrated extensive cerebral reorganization in cortical areas, showing how auditory areas of the brain are activated by visual stimuli in deaf persons, [3] while the visual cortex is activated by somatosensory and auditory stimuli in blind persons. [5,28,31,32] Our fi ndings could be ascribed to this form of neuroplasticity, CMP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Neville et al reported changes in evoked visual response in congenitally deaf persons and interprfeted it as a neuroplastic change, in which visual input invades unused areas of the auditory cortex. [27] These fi nding were later confi rmed in studies of subjects with single sensory deprivation (auditory or visual) using neuroimaging techniques with greater spatial resolution (fMRI and PET), [5,[28][29][30] which demonstrated extensive cerebral reorganization in cortical areas, showing how auditory areas of the brain are activated by visual stimuli in deaf persons, [3] while the visual cortex is activated by somatosensory and auditory stimuli in blind persons. [5,28,31,32] Our fi ndings could be ascribed to this form of neuroplasticity, CMP.…”
Section: Discussionmentioning
confidence: 99%
“…Auer et al (2007) reported somatosensory activation overlapping atlas-defined Heschl's gyrus in a deaf group relative to fixation, but ROI analysis was not performed making it difficult to determine whether responses were in primary auditory cortex. A magnetoencephalography (MEG) study using source modeling in a single elderly deaf person reported somatosensory responses were accounted for by a source in auditory cortex (Levänen et al, 1998) although the spatial precision of MEG is lower than that of fMRI, making more precise localization problematic.…”
Section: Discussionmentioning
confidence: 99%
“…One is a magnetoencephalography (MEG) study of one deaf person showing a source in auditory cortex responded to vibrotactile stimulation (Levänen et al, 1998). The second study, a vibrotactile fMRI study of six deaf adults with extensive hearing aid use, was analyzed as a spatial average, and responses to vibrotactile stimulation occurred in deaf Heschl's gyrus (Auer et al, 2007). Both studies provide evidence that deaf auditory cortex may respond to somatosensory stimulation, but they are limited in anatomical precision.…”
Section: Introductionmentioning
confidence: 99%
“…HL results primarily in a decline in auditory speech perception (Humes & Roberts 1990); however, changes in visual perceptual abilities indicate that adaptation to HL is not limited to the auditory modality. On the one hand, younger adults with early-onset hearing impairment are better at lipreading sentences than controls (Auer et al 2007), but even in normal-hearing (NH) people, this ability declines with age (Cienkowski & Carney 2002;Hay-McCutcheon et al 2005;Sommers et al 2005). Although investigations of unimodal perception in isolation help us understand how HL in older adults affects auditory and visual abilities, everyday perception for most people involves the combination of these inputs.…”
Section: Introductionmentioning
confidence: 99%